Representation of Cultural Elements in the Film Panggil Aku Ayah and the Korean Film Pawn: A Comparative Literature Study - Putu Keisya Permana Putri; Hikmah Aulia (International Journal Labs, 2026)
The film Panggil Aku Ayah (2025) is an Indonesian adaptation of the South Korean film Pawn (2020), which goes beyond mere narrative transfer by engaging in a process of transcreation to align the story with the socio-cultural context of Indonesian audiences. Rather than simply reproducing the original plot, the adaptation reinterprets cultural meanings, values, and social relations to ensure cultural relevance and emotional resonance within a different national setting. This research aims to compare the representation of cultural elements in Panggil Aku Ayah and Pawn using a comparative literature approach. The study employs a qualitative descriptive method, drawing on C. Kluckhohn’s theory of seven universal cultural categories as an analytical framework. The findings reveal significant transformations in five key cultural elements: the language system, which adapts dialogue and expressions to local linguistic norms; the livelihood system, which reflects differences in economic activities and social class structures; the religious system, which incorporates local beliefs and practices; the knowledge system, which reshapes moral education and life values; and social organization, which highlights distinct family structures and community relations. The study concludes that cross-cultural film adaptation functions as a creative strategy to embed local cultural identity, enabling global narratives to remain meaningful, accessible, and relevant to Indonesian audiences while preserving the emotional core of the original work.